Challenges of Second and Foreign Language Education in a Globalized World Studies in Honor of Krystyna Droździał-Szelest (Second Language Learning and Teaching, 2018)
This edited collection brings together papers by eminent scholars who attempt to demonstrate how challenges can most successfully be ameliorated with an eye to enhancing the effectiveness of the processes of language teaching and learning. In Part One, emphasis is placed on challenges that second language education has to face, both those more general, dealing with language policy issues, and those more specific, concerned with instructional options in the language classroom. Part Two focuses on challenges involved in researching the processes of teaching and learning in the second and foreign languages classroom, both with respect to research methodology and efforts to tap some variables impinging upon the effects of instruction. Finally, Part Three is devoted to challenges involved in second and foreign language teacher education, the quality of which to a large extent determines the outcomes of second language education in any educational context.